PENGARUH PERLAKUAN ISTIMEWA, PERSEPSI INVESTASI HUBUNGAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KUALITAS HUBUNGAN (STUDI KASUS PT. BPD DIY CABANG WATES) - Muhammad Tahwin; Septarani Prasiwi (BBM (Buletin Bisnis & Manajemen), 2016)
This study aims to analysis the preferential treatment, perceived relationship investment, and interpersonal communication as key factors influencing relationships quality. Analysis was performed on PT. BPD DIY Cabang Wates. A quantitative approach is employed. The data gathered using a survey method with questionnaire as an instrument of measurement. Scale which used to measure the answers of questionnaires questions using a likert scale with n=220 respondents as the samples. The data were analyzed using multiple regression analysis. Preferential treatment, perceived relationship investment, and  interpersonal communication found have a positive significant impact on the relationship quality in PT. BPD DIY Cabang Wates. Keywords: preferential treatment, perceived relationship investment, interpersonal communication, and relationships quality